PENGARUH PENGENDALIAN INTERNAL DAN INTEGRITAS PADA KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Kasus Pada Dinas SKPD Kota Mataram) - Decy Wulan Singgih; Ni Nyoman Yuliati; Rusli Amrul (Jurnal Aplikasi Akuntansi, 2017)
This study aims to determine the Influence of Internal Control and Integrity on Fraud Accounting Trend (Case Study on SKPD Office of Mataram City). This type of research includes associative research. The population used is the employees who are on the SKPD Office of Mataram City, while the number of samples taken are as many as 60 employees who are at the Office SKPD Mataram using purposive sampling techniques. Data collected are primary data in the form of questionnaire. The data has been collected and then analyzed using multiple linear regression analysis, by utilizing SPSS for Windows application program. The result of data processing shows that the internal control and integrity variables have a negative and significant effect on accounting fraud. Next for internal control and integrity variable simultaneously have significant effect on the tendency of accounting fraud in office SKPD Kota Mataram.